Pulmonary Alveolar Microlithiasis: A Review of a Rare Disease Through Rarely Discussed Perspectives - Altınışık, Göksel; Yiğit, Nilüfer; Çetin, Nazlı (Seminars in Respiratory and Critical Care Medicine, 2025)
Pulmonary alveolar microlithiasis (PAM) has been well characterized in terms of its description, genetic background, and diagnostic process for decades; however, no effective prevention or treatment has yet been established. PAM is classified as an ultrarare lung disease linked to mutations in the autosomal recessive sodium–phosphate co-transporter gene SLC34A2, which may serve as a potential target for future therapies. As new variants of SLC34A2 mutations continue to be identified, a broader genetic understanding could help predict the variable clinical course among patients and guide the development of therapies beyond palliative care. The creation of a disease severity score would be valuable for assessing disease burden, stratifying patients, and designing research studies. Given the clinico-radiological dissociation and heterogeneity of PAM, such a score should be developed as a composite index. Coupled with objective severity measures and identification of factors underlying individual variability, this approach could enhance insight into preventive and therapeutic strategies. Clinical advances in PAM remain limited, underscoring the need for international registries and cohorts as an urgent priority. Systematic re-evaluation of diagnosed cases and structured follow-up, rather than arbitrary visits, would generate standardized data critical for future research. A standardized patient evaluation form may facilitate the collection of data in a shared database.
Keywords: pulmonary alveolar microlithiasis; pathogenesis; lung transplantation; treatment; registry; future perspective